Does the income of the chief executive officer affect the quality of corporate financial statements? An evidence from industrial firms in Vietnam - Quyen Thuc Doan; Tran Thi Nguyet Nga; Le Thi Men; Susilo Nur Aji Cokro Darsono (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This study examines the relationship between the CEOs’ income and the quality of financial statements of industrial firms listed on the Ho Chi Minh Stock Exchange (HSX) during the three years from 2018 to 2020.Design/Methodology/Approach: This study investigated the influence of CEOs’ characteristics, particularly their income, on the quality of financial statements of listed firms in the Vietnamese industry by using features of information quality proposed by the International Accounting Standards Board (IASB). Ordinary Least Squares (OLS), Random Effects model (REM), Fixed Effects model (FEM), and Feasible Generalized Least Squares (FGLS) regressions were applied for empirical examinations.Research findings: The results of this study demonstrated that a CEO’s income positively affected the quality of corporate financial statements. Additionally, the analysis results confirmed the positive correlation between the firm’s size and the quality of disclosed reports, consistent with prior studies. However, this study uncovered that Big4 auditors did not influence the quality of financial statements.Theoretical contribution/Originality: This study contributes to the literature by providing a comprehensive perspective on the assessment of corporate financial statements quality and examining its association with the CEO’s income in the context of an emerging economy.Practitioner/Policy implication: The study is useful for investors and other financial statement users to assess the quality of corporate financial statements through the CEO’s profile; it also contributes as a scientific basis for firms to adjust the compensations offered to their CEOs.Research limitation: This study was limited by looking at the mono-directional impact of the CEO’s income on the financial statement quality. The following studies need a larger sample of industries and countries to strengthen the research findings. Also, further studies can broaden their perspectives to investigate the multidimensionality of this relation.